A Phase 1 Study to Assess the Relative Bioavailability of Two Capsule Formulations of Ixazomib, an Oral Proteasome Inhibitor, in Patients With Advanced Solid Tumors or Lymphoma. (7th August 2017) - Hanley, Michael J.; Gupta, Neeraj; Venkatakrishnan, Karthik; Bessudo, Alberto; Sharma, Sunil; O'Neil, Bert H.; Wang, Bingxia; van de Velde, Helgi; Nemunaitis, John
Abstract: The oral proteasome inhibitor ixazomib is approved in multiple countries in combination with lenalidomide and dexamethasone for the treatment of patients with multiple myeloma who have received at least 1 prior therapy. Two oral capsule formulations of ixazomib have been used during clinical development. This randomized, 2‐period, 2‐sequence crossover study (Clinicaltrials.gov identifier NCT01454076) assessed the relative bioavailability of capsule B in reference to capsule A in adult patients with advanced solid tumors or lymphoma. The study was conducted in 2 parts. In cycle 1 (pharmacokinetic cycle), patients received a 4‐mg dose of ixazomib as capsule A or capsule B on day 1, followed by a 4‐mg dose of the alternate capsule formulation on day 15. Pharmacokinetic samples were collected over 216 hours postdose. After the pharmacokinetic cycle, patients could continue in the study and receive ixazomib (capsule B only) on days 1, 8, and 15 of each 28‐day cycle. Twenty patients were enrolled; of these, 14 were included in the pharmacokinetic‐evaluable population. Systemic exposures of ixazomib were similar after administration of capsule A or capsule B. The geometric least‐squares mean ratios (capsule B versus capsule A) were 1.16 for Cmax (90% confidence interval [CI], 0.84–1.61) and 1.04 for AUC0–216 (90%CI, 0.91–1.18). The most frequently reported grade 3 drug‐related adverse events were fatigue (15%) and nausea (10%); there were no grade 4 drug‐related adverse events. These results support the combined analysis of data from studies that used either formulation of ixazomib during development.